The Effect of Personal Financial Education on Knowledge, Attitude, and Behaviour Finance Student Cenderawasih University Jayapura - Grace (Value Relevance: Jurnal Akuntansi, 2024)
This research aims to analyze the influence of personal financial education on the Knowledge, Attitude, and behaviour of finance students at Cenderawasih University, Jayapura. This type of research is explanatory research to test the hypothesis between personal financial education variables on Knowledge, Attitude, And behaviour finance. The population of this study was students at Cenderawasih University in the fourth semester, with a sample of 65 respondents. The research sample was tested using multivariate analysis with the help of SmartPls Ver software. 3. The research results show that personal financial education affects Knowledge, Attitude, And behaviour in finance. The research model can explain the influence of personal financial education on Knowledge by 29.2 %, personal financial education on attitudes by 18.2%, and personal financial education on financial behaviour by 19.2%